Increasing Psychological Hazards and Its Scope in Homoeopathy (Homoeopathy for All, 2022)
As we all know increasing tension  excessive use of mobiles ongoing disease  such as deaths of loved ones; love  betrayal; work-related stress, bullying  and harassment, lone or remote working,  violence in the workplace (both from  staff and students), fatigue, alcohol and  drug use; sedentary lifestyle; background  radiations; segregate families and many  more factors are continuously contributing  to psychological hazards. These are leading to various common  diseases such as anxiety disorders;  mood disorders; sycotic diseases;  dementia; eating disorders; ptsd; ocd’s;  schizophrenia are the few of these  innumerable diseases.
Keywords: harassment; schizophrenia; diseases